Islamic Ethics in Business Management: the Case of Transacting Parties - Issoufou, Chaibou (International Journal of Engineering and Technology, 2018)
Purpose: This paper aims to examine and explore Islamic ethics in business management and transaction pertaining to transacting parties. Design/methodology/approach: The paper adopts the qualitative research methodology to analyse data concerning issues related to the topic. Findings: This research paper finds that Islamic business ethics and management reflect the parties involved in the transaction because when the parties are dealing with each other, they have to observe the principles and instructions of al-Qur’an and al-Sunnah which are concerning business transaction and management. Research limitations/implications: This paper emphasises on the transacting parties in business management and Islamic ethical influence on them and the society at large. The paper suggests to conduct empirical research on the theme for more information and finding out the practical influence of Islamic business ethics and management on the transacting parties and market movement. Originality/value: The paper focuses on the parties involving in the business transaction. It also finds that following principles and instructions of al-Qur’an and al-Sunnah in business management play a crucial role and influence on transacting parties and community. Those principles and regulations are milestones for the success of the business transaction. This can make the paper as exclusive and distinctive in this research field.